1997
DOI: 10.1080/00288330.1997.9516794
|View full text |Cite
|
Sign up to set email alerts
|

Summer light‐trap catches of adult Trichoptera in hill‐country catchments of contrasting land use, Waikato, New Zealand

Abstract: The distribution of adult Trichoptera in light traps was investigated alongside nine streams draining catchments under native forest, pine forest, or pasture near Hamilton, Waikato, New Zealand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
9

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 21 publications
0
48
0
9
Order By: Relevance
“…Alterations to land use have many effects on streams, including changes to water temperature (Quinn et al 1992(Quinn et al , 1997Rutherford et al 1997), sediment loading (Allan etal. 1997), community composition of both invertebrates (Harding & Winterbourn 1995;Collier et al 1997) and fish (Hanchet 1990). In particular, pasture streams can be expected to have greater autochthonous production than native bush streams, because of the absence of shading and smaller inputs of allochthonous detritus in the former, with consequences for aquatic food chains (Bird & Kaushik 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations to land use have many effects on streams, including changes to water temperature (Quinn et al 1992(Quinn et al , 1997Rutherford et al 1997), sediment loading (Allan etal. 1997), community composition of both invertebrates (Harding & Winterbourn 1995;Collier et al 1997) and fish (Hanchet 1990). In particular, pasture streams can be expected to have greater autochthonous production than native bush streams, because of the absence of shading and smaller inputs of allochthonous detritus in the former, with consequences for aquatic food chains (Bird & Kaushik 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Focusing attention on the adult phase of the life cycle has highlighted the importance of the structure of the terrestrial habitat for mating, resting and egg maturation (Kovats et al, 1996) and for entry into terrestrial food webs (Svensson, 1974;Jackson and Resh, 1989;Ormerod and Tyler, 1991). Adult trapping integrates catches from a wider range of aquatic habitats and reflects corridor land-use and, consequently, can be used as a useful tool for bioassessment (Collier et al, 1997). This study shows how the collection of adult Trichoptera using non-attracting Malaise traps can provide the necessary data on community structure and taxonomic rigour, to assess the conservation status of small streams.…”
Section: Conservation Statusmentioning
confidence: 99%
“…There have been some important papers on small streams (e.g. Williams et al, 1992), but until recently there was little information about adults in small streams (Svensson, 1974;Collier et al, 1997;Collier and Smith, 1998;Griffith et al, 1998;Petersen, et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…It led to the development of a conceptual model for the effects of land-use change on hyporheic habitat, the testing of which is the subject of current studies at Whatawhata. Collier et al (1997) demonstrated strong landuse influences on adult caddisfly faunas. As with the benthic faunas (Quinn et al 1997a), the composition of adult caddisfly faunas differed most between the native forest and pasture sites with pine forest sites intermediate between these.…”
Section: Overview Of Special Issue Papersmentioning
confidence: 99%